Detection of Pyuria by Microscopic Urinalysis as a Marker of Pediatric Urinary Tract Infection - Shrestha, Dhiraj; Thapa, Pratigya; Bhandari, Dinesh; Bhattachan, Balkrishna; Parajuli, Hiramani; Chaudary, Prakash; Sharma, Vijay Kumar; Shah, Pradeep Kumar (Nepal Journal of Biotechnology, 2019)
Globally, different diagnostic tests of urinary tract infection (UTI) are in clinical practices. A reliable test can increase the efficiency of the healthcare system, especially in a developing country like Nepal, reducing cost and time. Thus, we accessed the possibility of pyuria detected by microscopic urinalysis as a marker of pediatric UTI. The prospective study was conducted fromJuly2014 to January 2015 at Alka hospital, Lalitpur. Microscopic urinalysis of 353clean-catch urine samples was done by the wet mount method, followed by urine culture by a semi-quantitative method. We confirmed 64 (18.1%) UTI cases by culture, the gold standard for UTI diagnosis. Fever was the most common clinical manifestation in UTI cases. The sensitivity, specificity, positive predictive value and negative predictive value of pyuria detected by microscopic urinalysis to identify UTI were 50%, 70.9%, 27.6% and 86.5% respectively. In 318 febrile cases, the sensitivity, specificity, positive predictive value and negative predictive value of pyuria detected by microscopic urinalysis to identify UTI were 73.2%, 72.6%, 28.3% and 94.8% respectively. The findings suggest pyuria detected by microscopic urinalysis as not a worth while marker of pediatric UTI. But it is a trust worthy marker in febrile pediatric cases.